El oso andino en los Andes centrales de Perú: presencia, interacción humano-oso y su percepción en La Mar, Ayacucho - Cardenas Badajos, Susan Mayra (2023)
In the present study, we determine the presence of the Andean bear Tremarctos ornatus and its interaction with humans in three communal territories of the La Mar province (Ayacucho). Between September and October 2019, we established a total of 22 transects to identify signs of the species, interviewed the local population about their interactions with the bear, and finally inspected livestock carcasses whose deaths were attributed to attacks by the species. In total, 312 signs of the Andean bear were recorded, with the majority being food remains, primarily found in the high puna areas above the montane forests. Local residents are familiar with and have encounters with the Andean bear in the field, and they identified recurring threats to the bear, including grassland fires, timber extraction, and livestock farming. They also reported that bears cause damage to crops and livestock. However, there were not enough pieces of evidence to confirm that the Andean bear had attacked any of the seven livestock carcasses evaluated. Still, a potential manipulation or consumption was identified in one of these cases. Our results emphasize the importance of combining bear presence surveys with observations from the local population to identify threats and mitigate potential human-bear conflicts based on unconfirmed events.